Essays in Industrial Organisation: Market Structure, Non-Price Strategies and Welfare. - Voudon, Benoit (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2021)
This dissertation consists of three essays in industrial organisation theory. It examines the relationship between market structure, welfare and firms' non-price strategies. The first essay discusses the impact of the level of vertical integration on the timing of adoption of a cost-reducing technology. Combining the technology adoption and vertical relations literatures in a simple duopoly model, I compare the technology adoption patterns under different exogenous vertical structures. First, I show that the influence of vertical integration on the technology adoption decision by one firm is significantly influenced by the vertical structure of the other firm. Second, I consider the two main types of technology adoption games under an asymmetric set-up and broaden the understanding of the underlying mechanisms for the solving of such games. Finally, I develop an industrial policy aimed at encouraging firms to adopt the technology at the socially optimal timing. The second essay is a continuation of Chapter 1 as it examines vertical integration incentives in the presence of a cost-reducing technology. Using the same model, I show that even in a purely symmetric set-up with no synergies or foreclosure incentives, an asymmetric integration equilibrium in which only one firm chooses to vertically integrate can arise. Then, comparing preemption and precommitment game, I show that the asymmetric equilibrium may exist under both types of game. Finally, I show that while vertical integration generally reduces consumer surplus, the market often maximizes societal welfare. The third essay develops a theoretical framework in order to understand the impact of the competition of heterogeneous retailers (internet versus brick-&-mortars) on market structure, profits, consumer surplus and societal welfare. First, I show that a patient online retailer may find it profitable to invest aggressively in delivery services and lower its price in order to exclude a physical competitor from the market. Second, I show that such strategy is particularly profitable if the online firm is allowed to build its own physical store in a densely populated area post-exclusion. Finally, I show that while consumers benefit from such predatory strategy when they are sufficiently impatient, society is generally worse off.
APPROVED
Keywords: Economics; Industrial Organisation; Vertical Integration; Technology Adoption; Predation; Retail Apocalypse